Adsorptive removal of ni2+ from aqueous solution onto rice husk-based activated carbon - Taha, M.F. (Trans Tech Publications Ltd, 2014)
The potential of rice husk-based activated carbon (RHAC) as an alternative low-cost adsorbent for the removal of Ni2+ from aqueous solution was studied. RHAC was prepared via chemical treatment using NaOH followed by the carbonization process. The textural properties of rice husk-based activated carbon, i.e. surface area (253 m2/g) and pore volume (0.17 cm2/g), were determined by N2 adsorption. The adsorption studies to remove Ni2+ from aqueous solution using RHAC were carried out at a fixed initial concentration of Ni2+ (150 ppm) with varying RHAC as a function of contact time at room temperature. The concentration of Ni2+ was determined by atomic absorption spectrophotometer (AAS). The maximum removal of Ni2+ was increased from 40 to 89 when the amount of RHAC was increased from 0.1 g to 0.5 g. The isotherm and kinetic analyses showed that equilibrium data of adsorption studies fitted well Langmuir, Freundlich and second order kinetic models. Â© 2014 Trans Tech Publications, Switzerland.